Democracy and Islamic Da'wah: : Study of the Politicization of Religion in the 2024 General Election in East Lombok Regency - Hamzani, Yusri (STAI Darul Kamal NW Kembang Kerang, 2025)
This article looks at the politicization of religion in East Lombok Regency during the 2024 elections. The author collected data in the field using three techniques: observation, interviews, and documentation. These three strategies generate primary sources. Meanwhile, secondary sources include scholarly publications such as journals, dissertations, scientific periodicals, and survey findings. After completing research, the author discovered that religion was politicized in East Lombok Regency through the use of religious symbols such as the imamah and white peci as traditional apparel that represents piety. Politicians also employ the narrative of friendship, politics as a platform for da'wah, ukhuwah Islamiyah, piety, and sami'na wa atho'na to politicize religion. Aside from that, their identity as a Tuan Guru is also used on pamphlets, billboards, stickers and even on ballot papers.